PENGENDALIAN KUALITAS PRODUK FILTER BAHAN BAKAR DENGAN MENGGUNAKAN METODE SIX SIGMA - Rio Alfandy; Helena Juliana Kristina; Doaly, Carla Olivia (Jurnal Mitra Teknik Industri, 2023)
PT. ABC is a company engaged in the manufacture of automotive spare parts and machinery. Based on the results of interviews and observations, it is known that there are problems regarding the large number of product defects produced when producing fuel filters of 3.84%. The purpose of this research is to improve the quality of producing fuel filter products using the six sigma method to identify, analyze and provide several suggestions for improvement. The most common types of product defects are broken filters, non-centered filters and reject settings. Based on the results of data processing, the Cp value was 0.96, the Cpk was 0.88, the DPMO was 12788 units and the sigma value was 3.73. Then implemented the proposed improvements in the form of making a checksheet, one point lesson and parameter standardization. The results of calculations performed at the control stage are the p control chart showing that the data is more stable, the process capability value increases to 1.17 and 1.11, the DPMO value decreases to 11652 and the sigma value increases to 3.76. This shows that the implementation has succeeded in improving the quality of producing fuel filters.